Análisis de Seguridad en la Red de Datos de la Empresa SERVICON - Cano Alava, Jennifer Mercedes (2017)
At present for many companies or organizations it is essential to incorporate into their structure the implementation of computer technology, in order to automate, organize and optimize the resources and information generated. But this reality will not be fruitful, without an adequate information security policy. SERVICON is an accounting and tax consulting firm that has a small data network, with a very considerable traffic of data and sensitivity of the information that is handled. The same one that presents certain vulnerabilities and inconsistencies in computer security, becoming present with loss of data, duplication of information and uncontrolled access of the users. The present case study makes it possible to highlight and study these weaknesses in the data network, the tasks and activities of the users in the network and the configurations of the equipment and software; being the case of the MÓNICA application, which manages most of the information of the company and its clients. Finally verify that there is an adequate management of backup and recovery of the Database of the accounting program and if not exist, suggest the implementation of backup policies, techniques of encryption of information in the Database and allocation of user accounts with roles and privileges.